Examining the Influencing Factors of Exercise Intention Among Older Adults: A Controlled Study Between Exergame and Traditional Exercise - Wu, Zumei (2015)
Promoting physical activities among older adults becomes an important component of successful aging. The aim of this study was to assess the influence of both exercise settings and player interaction patterns on exercise intention in a sample of Asian older adults. A 2×2 (exercise settings: traditional exercise vs. exergame×player interaction patterns: collaborative vs. competitive play) between-subjects experimental intervention was conducted with 113 Singaporean older adults for 1 month. An interviewer-administered questionnaire survey was issued to measure key variables of enjoyment, social presence, and perceived behavioral control. The findings supported the importance of social presence and perceived behavioral control in older adults' exercise prediction, and highlighted the effect of collaborative play in older adults' exercise promotion. Compared with traditional exercise, the effect of exergames on motivating older adults to exercise was significantly lower. The findings of this study revealed rich directions for future elderly exercise research, and provided strategies that could be applicable for policy making and game design to promote elderly exercise participation.